Pengaruh Model Pembelajaran Example Non Example dan Motivasi Belajar Siswa terhadap Keterampilan Menulis Teks Prosedur - Lasri Maisa Putri; Syahrul Ramadhan (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
This experimental research was motivated by a problem in learning Indonesian: the low score of students' learning outcomes in writing procedural texts. Based on this, this research was conducted to know the effect of the Example Non Example learning model and learning motivation on the skills of writing procedure text. The samples of this study were students in grade 7-I (experimental class) and grade 7-H (control class) at MTs Negeri 4 Pasaman Barat for the academic year 2020/2021. The data of this research are the score of the learning motivation questionnaire and the test scores for writing procedural text writing skills in the experimental and control classes. The final results of this study indicate that the Example Non Example learning model has a good effect on the writing skills of the seventh-grade students of MTs Negeri 4 Pasaman Barat. It can be seen from the scores of students' procedural text writing skills taught using the Example Non Example cooperative learning model better than students taught using conventional learning models. Furthermore, there is also an interaction between the Example Non-Example learning model and learning motivation so that students can write procedure texts better.